Delivering A Transformational Learning Experience Online - Vergara, Raymond Allan (Future Science / FSH-PH Publications, 2022)
This study aims to explore how to deliver a transformational learning experience in an online classroom. Using qualitative action research, it examined expectations and experience of learners who participated in an online event marketing undergraduate course for a term. This study finds that experiential lessons, such as storytelling lectures and collaborative project requirements, and the teacher’s caring attitude and enthusiasm help learners master concepts, enhance skills, and develop positive attitudes, values, and beliefs towards learning. It also finds that teachers should focus on nurturing learner engagement to keep them motivated and persist in the course. This study contributes to the discussion on event marketing and management pedagogy, transformational teaching, and transformative learning experience.